The Relative Contribution of Non-Foliar Organs of Cotton to Yield and Related Physiological Characteristics Under Water Deficit - Yuan-yuan HU; Ya-li ZHANG; Xiao-ping YI; Dong-xia ZHAN; Hong-hai LUO; Chow Wah Soon; Wang-feng ZHANG (Journal of Integrative Agriculture, 2014)
Water deficit is one of the most important causes of decreased yield in cultivated plants. Non-foliar green organs in cotton play an important role in yield formation at the late growth stage. Although better photosynthetic performance was observed in a non-foliar organ (bract) compared with leaves under water deficit. However, the physiological response of each organ in cotton to water deficit has not been comprehensively studied in relation to the water status and photosynthesis characteristics. We studied the maintenance of water status of each organ in cotton by measuring their relative water content, proline content and stomatal characteristics. Water deficit significantly decreased the surface area of each organ, but to a lesser extent in non-foliar organs. Our results showed that the relative contribution of biomass accumulation of non-foliar organs increased under water deficit. Non-foliar organs (bracts and capsule wall) showed less ontogenetic decrease in O2 evolution capacity and in RuBPC activity (per dry weight) as well as better antioxidant systems than leaves at various days after anthesis. We conclude that the photosynthesis from non-foliar organs is important for increasing cotton yield especially under water deficit conditions.